Design of selective COX-2 inhibitors in the (aza)indazole series. Chemistry, in vitro studies, radiochemistry and evaluations in rats of a [18F] PET tracer - Jonathan Elie; Johnny Vercouillie; Nicolas Arlicot; Lucas Lemaire; Rudy Bidault; Sylvie Bodard; Christel Hosselet; Jean-Bernard Deloye; Sylvie Chalon; Patrick Emond; Denis Guilloteau; Frédéric Buron; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry, 2019)
A series of novel derivatives exhibiting high affinity and selectivity towards the COX-2 enzyme in the (aza) indazole series was developed. A short synthetic route involving a bromination/arylation sequence under microwave irradiation and direct C–H activation were established in the indazole and azaindazole series respectively. In vitro assays were conducted and structural modifications were carried out on these scaffolds to furnish compound 16 which exhibited effective COX-2 inhibitory activity, with IC50 values of 0.409 µM and an excellent selectivity versus COX-1. Radiolabeling of this most potent derivative [18F]16 was achieved after boron ester release and the tracer was evaluated in vivo in a rat model of neuroinflammation. All chemistry, radiochemistry and biological experimental data are discussed.